The WTO Agreement and Telecommunications Policy Reform - Cowhey, Peter F. 1948- (The World Bank, 2001)
Happily, the revolution going on in the telecommunications industry is benign. Technological change and competition are making possible changes considered improbable even 15 years ago. The WTO Agreement on Basic Telecommunications Services created a new regime for the world market. Now we must pay close attention to regulatory fundamentals. Every country serious about introducing competition finds that the transition from monopoly to competition is both economically rewarding and laden with policy dilemmas. As a new century begins, we have an essentially new market for telecommunications. Digital technology forced a reexamination of the opportunity costs of protecting traditional telecommunications equipment and service suppliers. An inefficient market for telecommunications threatened competitiveness in the computer, software, and information industry markets. Meanwhile, after dislocations created by global stagflation through the early 1980s, developing countries became interested in privatization of state enterprises as a tool of economic reform - and state telephone companies were especially promising targets for privatization. Those countries began exploring options for allowing selective competition, as phone companies in major industrial countries began looking to foreign markets for new business opportunities. The WTO Agreement on Basic Telecommunications Services created a new regime for the world market. Now we must pay close attention to regulatory fundamentals: - Low barriers to entry in the market for communications services. - Effective rebalancing of rates for services during the market transition. - Strong interconnection policies. - The creation of independent regulatory authorities with the resources and power necessary to foster competition and safeguard consumer welfare.